2017
DOI: 10.1155/2017/5939810
|View full text |Cite
|
Sign up to set email alerts
|

The Channel Estimation and Modeling in High Altitude Platform Station Wireless Communication Dynamic Network

Abstract: In order to analyze the channel estimation performance of near space high altitude platform station (HAPS) in wireless communication system, the structure and formation of HAPS are studied in this paper. The traditional Least Squares (LS) channel estimation method and Singular Value Decomposition-Linear Minimum Mean-Squared (SVD-LMMS) channel estimation method are compared and investigated. A novel channel estimation method and model are proposed. The channel estimation performance of HAPS is studied deeply. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…While satellite models like the CCIR model [133], [134] and FSPL model can be seen as too pessimistic and optimistic respectively, the use of FSPL with some realistic shadowing can potentially give reasonable results. Further studies on HAP channels can be found in [119], [120], [135].…”
Section: B Factors Affecting Coverage Extensionmentioning
confidence: 99%
“…While satellite models like the CCIR model [133], [134] and FSPL model can be seen as too pessimistic and optimistic respectively, the use of FSPL with some realistic shadowing can potentially give reasonable results. Further studies on HAP channels can be found in [119], [120], [135].…”
Section: B Factors Affecting Coverage Extensionmentioning
confidence: 99%
“…However, the cost of the anchor node is higher than that of ordinary nodes. If 10% of the nodes are anchor nodes, the price of the network will increase 10 times [8][9][10][11][12][13]. However, when the unknown node is located, it will no longer need expensive anchor nodes.…”
Section: Background and Researchmentioning
confidence: 99%